A Systematics Literature Review on The Use of 3D Models in Colombian Ethnomathematics - Jonathan Alberto Cervantes Barraza; Lisnani Lisnani (Journal of Emerging Technologies in Ethnomathematics, 2025)
This paper presents a systematic literature review on the ethnomathematics of Colombia using 3D modeling technologies. It aims to identify and synthesize the mathematical ideas embedded in Colombian cultural artifacts, traditions, and practices, especially relating to geometry and spatial reasoning. The methodology follows PRISMA guidelines, analyzing peer-reviewed articles, dissertations, and ethnographic reports. Data was coded thematically, focusing on cultural representations of geometry and their transformation into 3D visual models. Results show that Colombian indigenous and Afro-descendant communities integrate geometric concepts into textiles, housing structures, and ceremonial spaces. The use of 3D models helps visualize and preserve these practices while facilitating culturally relevant mathematics education. This study highlights the importance of integrating technology with ethnomathematics to support both heritage conservation and educational innovation.